Bleeding in Patients with Atrial Fibrillation Plus Coronary Artery Disease under Triple anti-Coagulant Therapy - Pishgahi, Mehdi; Rashidi, Marjan; Arefizade, Reza (Archives of Men's Health, 2021)
Introduction: Regarding scarce knowledge about bleeding in non-valvular atrial fibrillation (AF) patients with simultaneous coronary artery disease (CAD) under triple anti-coagulant therapy, this study was carried out to recognize the risk of hemorrhage and preventive programming. Materials and Methods: In this performed prospective, 150 consecutive patients with non-valvular atrial fibrillation and concurrent coronary disease, candidate for triple therapy with Asprin 80 mg, Clopidogrel 75 mg and Rivaroxaban 15 mg (in Shohada, Loghman, Modarres, and Labafinezhad centers, in Tehran, Iran during Jan 2019 to Jan 2020 were enrolled and the incidence rate of bleeding and compliance were evaluated for one month. Results: The results in this study demonstrated that 87.3% had compliance and completely use three drugs. Bleeding occurred in 0.6 % (4 patients), no major bleeding , only one minor bleeding as GIB, three minimal cases (totally 4 bleeding cases), 3 cases with epistaxis, 7 patients with ecchymosis, 6 subjects with hematuria, no one required discontinuation of drug. Diabetes mellitus, hypertension, female sex, older age, higher HASBLED Score, and higher CHADS-VASC Score were related to lack of compliance (P < 0.05). Conclusion: Incidence rate of bleeding in atrial fibrillation plus coronary concurrent patients, candidate for triple therapy with ASA, Clopidogrel and Rivaroxaban is low. Also the bleeding is minor and the compliance is high showing that majority of cases use routinely these triple therapy regimen.